2018
DOI: 10.1353/cpr.2018.0017
|View full text |Cite
|
Sign up to set email alerts
|

Building Resilience after Disasters through the Youth Leadership Program: The Importance of Community and Academic Partnerships on Youth Outcomes

Abstract: The YLP demonstrated how disaster response interventions supporting resilience-based leadership and empowerment influenced students' perceived ability to achieve goals fostering post-disaster resilience. Successful initiatives, such as the YLP, emphasize the importance of parallel and interactive individual, family and community support processes to enhance the recovery experience for both individuals and communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 30 publications
(32 reference statements)
1
35
0
Order By: Relevance
“…When school shuts down for prolonged periods, there can be profound and widespread effects, not just on individuals who are directly affected, but on the whole family, community and economy. This issue was widely noted after Hurricane Katrina, which closed schools in some areas of New Orleans for extended periods (Osofsky et al, 2018). Similarly, safe reopening of schools rapidly became a vital concern in countries around the world during the COVID‐19 pandemic.…”
Section: Influences On How Children Respond To Disastermentioning
confidence: 99%
See 1 more Smart Citation
“…When school shuts down for prolonged periods, there can be profound and widespread effects, not just on individuals who are directly affected, but on the whole family, community and economy. This issue was widely noted after Hurricane Katrina, which closed schools in some areas of New Orleans for extended periods (Osofsky et al, 2018). Similarly, safe reopening of schools rapidly became a vital concern in countries around the world during the COVID‐19 pandemic.…”
Section: Influences On How Children Respond To Disastermentioning
confidence: 99%
“…Programs that engage students to lead in school or community recovery appear to have multifaceted salutary effects on recovery after disasters. Students in the Youth Leadership Program implemented in the St. Bernard United School District after Katrina, who were engaged in meaningful recovery projects for their school and community, gained self‐efficacy and showed fewer trauma symptoms over time (Osofsky et al, 2018).…”
Section: Influences On How Children Respond To Disastermentioning
confidence: 99%
“…Furthermore, the out-of-province/state and international students are at even more risk of vulnerabilities than their peers due to lack of direct family support and local ties. All these vulnerabilities have, in the past and recently, pointed research toward observing young people as a vulnerable, passive, and dependent group, rather than addressing the diversity within this group, and addressing their strengths and leadership capabilities as well (Tanner and Doberstein 2015 ; Osofsky et al 2018 ).…”
Section: Female University/college Students and Disaster-specific Leadershipmentioning
confidence: 99%
“…Over time, the programme became part of the school system's mission in promoting a positive and healthy recovery environment for students. The YLP following Hurricane Katrina was recognised nationally as an important public–private partnership (Osofsky et al, 2018). In an evaluation of the programme, results indicated that students participating in the Youth Leadership Programme scored significantly higher on the measure of self‐efficacy than those not participating in the program (Osofsky et al, 2018).…”
Section: The Impact Of Hurricane Katrina On Children and Familiesmentioning
confidence: 99%
“…The YLP following Hurricane Katrina was recognised nationally as an important public–private partnership (Osofsky et al, 2018). In an evaluation of the programme, results indicated that students participating in the Youth Leadership Programme scored significantly higher on the measure of self‐efficacy than those not participating in the program (Osofsky et al, 2018). Interestingly, Varanasi (2019) also reported positive results from on a similar youth empowerment effort, the Skills, Hope, Opportunities, Recovery, and Engagement (SHOREline) program.…”
Section: The Impact Of Hurricane Katrina On Children and Familiesmentioning
confidence: 99%